The Newberry 125 stories of our collection - Spadafora, David 1951- (Newberry Library distributed by the University of Chicago Press, 2012)
To mark its 125th anniversary, the Newberry has assembled one hundred and twenty-five of its most significant objects in one beautifully illustrated volume. Arranged in order to tell both the story of the library as an institution and its collecting history, The Newberry 125 covers a great breadth of topics including: American culture throughout the ages; the history of Chicago and the Midwest; geography and exploration; religion; music and dance; Medieval and Renaissance studies; and the indigenous peoples of North America. Each of the highlighted items has been photographed in stunning full color and is accompanied by a brief description, its call number, and a concise yet informative essay by a Newberry curator, librarian, or researcher, on the object's importance to the collection." --amazon.com.